Effects of dorsal hippocampal damage on conditioning and conditioned-response timing: a pooled analysis - Tam, Shu K.E.; Jennings, Dómhnall J.; Bonardi, Charlotte (Wiley, 2015)
Behavioral findings suggest that the dorsal hippocampus (DHPC) plays a role in timing of appetitive conditioned responding. The present article explored the relationship between the extent of DHPC damage and timing ability, in a pooled analysis of three published studies from our laboratory. Initial analyses of variance confirmed our previous reports that DHPC damage reduced peak time (a measure of timing accuracy). However, the spread (a measure of timing precision) was unchanged, such that the coefficient of variation (spread/peak time) was significantly larger in DHPC-lesioned animals. This implies that, in addition to the well-established effect of DHPC lesions on timing accuracy, DHPC damage produced a deficit in precision of timing. To complement this analysis, different generalized linear mixed-effects models (GLMMs) were performed on the combined dataset, to examine which combinations of the different behavioral measures of timing were the best predictors of the degree of hippocampal damage. The results from the GLMM analysis suggested that the greater the DHPC damage, the greater the absolute difference between the observed peak time and reinforced duration. Nevertheless, this systematic relationship between damage and performance was not specific to the temporal domain: paradoxically the greater the damage the greater the magnitude of peak responding. We discuss these lesion effects in terms of scalar timing theory.